2015
DOI: 10.1111/anu.12262
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the optimal essential amino acid ratios in juveniles of Nile tilapia (Oreochromis niloticus) by the deletion method

Abstract: One of the strategies used to improve fish production is lowering the feed costs and the environmental impact by reducing dietary protein content. Using the deletion method, we determined the optimal amino acid (AA) ratio for Nile tilapia (Oreochromis niloticus) (body weight 20 g). Eleven experimental diets and four replications, taken two at a time, distributed in a randomized block design were used. For this trial, a balanced diet (BD) was formulated. Ten other diets were formulated by the deletion method, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
46
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 23 publications
13
46
5
2
Order By: Relevance
“…However, a lower dietary lysine requirement of 14 g/kg was reported in NRC (). Liebert and Benkendorff () estimated that the optimum lysine requirement was 15.5 g/kg which is similar to the value obtained by Diogenes et al () for Nile tilapia, whereas higher values of lysine requirements have been reported for Indian major carp Labeo rohita juveniles at 22.4 g/kg (Murthy & Varghese, ), African catfish Clarias gariepinus at 22.9 g/kg (Fagbenro, Balogun, Bello‐Olusoji, & Fasakin, ), Atlantic cod Gadus morhua at 23.8 g/kg (Grisdale‐Helland et al, ) and Chinese sucker Myxocyprinus asiaticus at 23.9 g/kg (Lin et al, ). Similarly, the dietary lysine requirement for maximum weight gain in juveniles of cobia Rachycentron canadum , silver perch Bidyanus bidyanus and stinging catfish Heteropneustes fossilis was reported at 23.8, 23.2 and 20 g/kg by Zhou, Wu, Chi, and Yang (); Yang et al (); and Khan (), respectively.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, a lower dietary lysine requirement of 14 g/kg was reported in NRC (). Liebert and Benkendorff () estimated that the optimum lysine requirement was 15.5 g/kg which is similar to the value obtained by Diogenes et al () for Nile tilapia, whereas higher values of lysine requirements have been reported for Indian major carp Labeo rohita juveniles at 22.4 g/kg (Murthy & Varghese, ), African catfish Clarias gariepinus at 22.9 g/kg (Fagbenro, Balogun, Bello‐Olusoji, & Fasakin, ), Atlantic cod Gadus morhua at 23.8 g/kg (Grisdale‐Helland et al, ) and Chinese sucker Myxocyprinus asiaticus at 23.9 g/kg (Lin et al, ). Similarly, the dietary lysine requirement for maximum weight gain in juveniles of cobia Rachycentron canadum , silver perch Bidyanus bidyanus and stinging catfish Heteropneustes fossilis was reported at 23.8, 23.2 and 20 g/kg by Zhou, Wu, Chi, and Yang (); Yang et al (); and Khan (), respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Amino acid requirements for tilapia were first determined by Santiago and Lovell (). In the last ten years, understanding of tilapia's amino acid requirements has been furthered with data on sulphur amino acids (Figueiredo‐Silva, Lemme, Sangsue, & Kiriratnikom, ; Nguyen & Davis, ) and on the ideal essential amino acid profile (Diogenes et al, ). Most of the studies confirm the assertion of Santiago and Lovell () that lysine is one of the most limiting AA in tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…Protein metabolism increased with increase in dietary protein levels and AA supplementation. It might be because a major part of weight increase is related to the protein retention, and protein increases establish equilibrium between protein anabolism and catabolism (Diogenes et al,2016). Abdel-Tawwab et al (2010) reported that protein metabolism, including PER, PPV, and PGR, were significantly (P>0.05) affected by protein levels in the diets.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional methionine requirement of tilapia is 0.7 % of the dietary protein. However, methionine is precursor of cystine, thus, it is recommended supplying 0.9 % methionine to tilapia diets, and CSM meal can then be a good methionine source of diets as it may supply up to 1.02 % digestible methionine (Diogenes et al, 2016;Michelato et al, 2013;Shiau, 2002).…”
Section: Amino Acid and Macronutrients Digestibility Of Chlorella Sormentioning
confidence: 99%
“…Dietary lysine considerably affects growth performance, health and retention of N by fish (Li et al, 2009;Diogenes et al, 2016;NRC, 2011;Shiau, 2002). Lysine contents of CSM are considerably high -5.17 % of Values determined by analysis ± standard error; As a matter of fact, Koprucu and Ozdemir (2005) reported ADCs of protein of 90 % and 87 % for anchovy meal (71 % CP) and soybean meal (53 % CP), respectively, for juvenile Nile tilapia (15 ± 0.1 g).…”
Section: Amino Acid and Macronutrients Digestibility Of Chlorella Sormentioning
confidence: 99%